2022
DOI: 10.12965/jer.2142716.358
|View full text |Cite
|
Sign up to set email alerts
|

Association among cognitive function, physical fitness, and health status in older women

Abstract: This study examined the association among cognitive function, physical fitness, and health status in healthy older women. Ninety-four females aged from 62 to 86 years (72.66 ± 5.38 years) from community healthcare centers and an exercise club in Seoul, South Korea. Cognitive function was assessed using the Seoul Neuropsychological Screening Battery. Physical performance comprised cardiorespiratory endurance, lower extremity strength, active balance ability, and walking speed. Health status included blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…However, findings on strength of the lower limb are lacking. We identified a study that linked memory capacity to lower limb strength, demonstrating that cognitive function can be associated with physical fitness 47 . A significant association was identified between the five-times-sit-to-stand test and cognitive performance, indicating that a performance duration of less than 15 s serves as a cutoff value for determining the presence of cognitive impairment 48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, findings on strength of the lower limb are lacking. We identified a study that linked memory capacity to lower limb strength, demonstrating that cognitive function can be associated with physical fitness 47 . A significant association was identified between the five-times-sit-to-stand test and cognitive performance, indicating that a performance duration of less than 15 s serves as a cutoff value for determining the presence of cognitive impairment 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Low muscle mass is strongly associated with low muscle strength [ 29 ]; thus, this might indirectly cause the loss in overall physical fitness. Fourth, cognitive function may be an important mediator between smartphone use and physical fitness because excessive smartphone use can cause cognitive function impairment [ 30 ], and better cognitive function is associated with better physical fitness [ 31 ]. Finally, it has been reported that excessive smartphone use is associated with poor sleep quality among Chinese college students [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measure of interest was for executive function among these studies Trail Making Test were used in 5 studies followed by the N-Back test for two studies. One study did not mention the type of test used for executive function (Kang, et al, 2022). All but one study (Kang, et al, 2022) reported a significant association between executive function and TUG.…”
Section: Association Between Executive Function Measures and Tugmentioning
confidence: 99%
“…One study did not mention the type of test used for executive function (Kang, et al, 2022). All but one study (Kang, et al, 2022) reported a significant association between executive function and TUG. People with better results on the TUG test performed better in executive measurement tests.…”
Section: Association Between Executive Function Measures and Tugmentioning
confidence: 99%